The determination of road sections by computer for use in road design - Keuck, Gerhard Helmut Max (Department of Civil Engineering, 2016)
A brief resume of ,recent developments in the design of roads is given with special reference to the increasing part played by automated methods by means of which higher degrees of optimization may be achieved. Flow charts illustrating road design demonstrate the relative importance of the determination of the transverse road section by computer. The finished transverse road section, called a template, consists of a central portion and the outer sloped cut and fill banks. The central portion covers the carriageway(s) and shoulders, the shape of which is predetermined by the geometric .design of the road surface and is independent of ground shape. The outer sloped banks, called the side-drain template, are dependent upon the position of the ground surface in relation to the predetermined central portion. When a road is to be built, the road authority usually prescribes the final transverse shape of the road by specifying a standard road template. At every point along the road a specific template can then be determined in accordance with the standard template. However, problems are experienced because certain available computer programs are unable to execute the side-drain portion of the standard road template correctly while earthwork quantities are being calculated. Several available programs are investigated with regard to the procedures adopted by them for the selection of appropriate road side-drain templates. Deficiencies in these programs are noted. A general solution to the problem of the logical determination of road sections by computer, namely, the method of the locus of the slope stake point, is introduced and elucidated. The success of the method is confirmed by the presentation of the completely operative computer program SHARM for the calculation of road earthworks quantities: The use of the program is demonstrated by a short sample run. Limitations of the method of the locus of the slope stake point and of the SHARM program are noted, and finally some future developments are discussed.